Transformasi Komunikasi Tatap Muka ke Komunikasi Digital melalui Facebook di Daerah Bangetayu Wetan RT 02 RW 08 Kecamatan Genuk Kota Semarang - Devananda Satria Nugraha; Suryanto Suryanto (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
Digital technology has significantly shifted communication patterns among the residents of RT 02 RW 08 Bangetayu, transitioning from traditional face-to-face interactions to digital spaces, particularly through Facebook groups. This study employs a qualitative method, utilizing observation, in-depth interviews with nine informants, and digital content analysis to explore this transformation. The findings show that, while direct communication still exists, digital interactions have become dominant due to their speed, expressive freedom, and coordination efficiency. This shift is largely driven by increased accessibility to digital platforms, the rise of digital culture, and the comfort of communicating without facing traditional social barriers. Residents are more inclined to engage online as it provides a sense of convenience and a platform for sharing opinions freely. However, the study also highlights a paradox where online participation has surged, while face-to-face conversations have declined, leading to challenges in maintaining social cohesion within the community. The study suggests that while digital communication offers many advantages, it is essential to find a balance between online and offline interactions to preserve the strong community ties that are fostered through personal, direct engagement. The implications of this research call for efforts to promote a hybrid communication model that integrates both digital and face-to-face interactions for the benefit of community building and social harmony